Urgency of Development and Awareness of Early Childhood Morals - Hazizah, Nur; Ariyanti, Erni (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2019)
The moral development of early childhood is a change in children's behavior from bad to good and occurs throughout the child's life. The method of instilling moral values in early childhood varies, depending on the character of each child. In the formal education pathway how to instill moral values in early childhood can be done through learning activities with a face-to-face schedule. For example, through Early Childhood Education. Whereas in the non-formal education pathway the inculcation of moral values in early childhood can be done through family education and education organized by the environment.Keywords: Moral Awareness, Early Childhood